Latitude, Planting Density, and Soil Available Potassium Are the Key Driving Factors of the Cotton Harvest Index in Arid Regions - Xiaopeng Yang; Wanli Yu; Qve Li; Dongdong Zhong; Jiajing He; Hegan Dong (Agronomy)
The lint harvest index (HI) of cotton is the ratio of cotton lint yield to the total aboveground biomass of cotton, which is not yet clear in arid-zone cotton areas. In 2022–2023, large-scale sampling was carried out in Xinjiang, and the HI of different variety types of cotton in Xinjiang and their key drivers were clarified using methods such as random forest modeling (RFM) and structural equation modeling (SEM). The results show that the overall cotton HI in Xinjiang ranged from 0.276 to 0.333 and 0.279 to 0.328 for the Xinluzao (XLzao) variety types, and from 0.276 to 0.333 for the Xinluzhong (XLzhong) variety types. The results of the SEM analysis show that the latitude (−0.99) and planting density (0.50), in the climatic geography factors, and available potassium in soil (0.88), in the soil nutrient factors, have the greatest effects on the overall cotton HI in Xinjiang. The key driving factors of cotton HI were found to be different among different variety types. This study aimed to clarify the HI of different variety types of cotton in arid-zone cotton and to explore its key driving factors. This was undertaken in order to provide a theoretical basis for the accurate estimation of cotton and cotton straw yields in the arid zone.